2023
DOI: 10.1007/s10584-023-03483-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring public acceptability of direct air carbon capture with storage: climate urgency, moral hazards and perceptions of the ‘whole versus the parts’

Abstract: Negative emission technologies (NETs) or the drawdown of atmospheric carbon is increasingly essential to meeting climate targets. Many options (e.g., afforestation) may not however meet the scale of removal and permanence of storage needed. Scientists and engineers are thus turning to new alternatives involving technology bundles using direct air capture of C0 2 and storage. However, the social acceptability of these is presumed unlikely given the sheer complexity of their components, governance arrangements, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…These practices are similar to current widespread offsetting practices, which are widely considered to be problematic [117]. DACCS has also historically been associated with various concerns about its risks, such as its large energy requirements [118,119], its safety [8,85,120], and its entanglement with the fossil fuel industry and perverse incentives to continue polluting [121][122][123], which reduce public acceptance of DACCS [6,120,124]. The benefits of DACCS, on the other hand, lie in its potential to not only enable net-zero greenhouse gas emissions in hard-to-abate sectors, but also to contribute to net-negative CO 2 emissions, although such impacts become climate-relevant only if absolute emissions fall below the rate of carbon removal [2,3,[5][6][7].…”
Section: Social and Behavioral Factorsmentioning
confidence: 75%
“…These practices are similar to current widespread offsetting practices, which are widely considered to be problematic [117]. DACCS has also historically been associated with various concerns about its risks, such as its large energy requirements [118,119], its safety [8,85,120], and its entanglement with the fossil fuel industry and perverse incentives to continue polluting [121][122][123], which reduce public acceptance of DACCS [6,120,124]. The benefits of DACCS, on the other hand, lie in its potential to not only enable net-zero greenhouse gas emissions in hard-to-abate sectors, but also to contribute to net-negative CO 2 emissions, although such impacts become climate-relevant only if absolute emissions fall below the rate of carbon removal [2,3,[5][6][7].…”
Section: Social and Behavioral Factorsmentioning
confidence: 75%
“…Extensive research has demonstrated that public groups tend to be skeptical of technologies that propose intervening in natural environments . This cautionary stance is particularly keen regarding coastal regions and the ocean, and negative opinion about ocean fertilization, among other proposed climate solutions, is common. , Public concerns regarding the proximity and security of a storage reservoir and worries about the health and environmental impacts of a potential leak are common but may be reduced when the permanence of CO 2 mineralization and ocean basalt storage is considered . Other concerns arise around environmental safety in the ocean, such as the infrastructure construction and related industrial responsibility …”
Section: Discussionmentioning
confidence: 99%
“…52,56 Public concerns regarding the proximity and security of a storage reservoir and worries about the health and environmental impacts of a potential leak are common but may be reduced when the permanence of CO 2 mineralization and ocean basalt storage is considered. 57 Other concerns arise around environmental safety in the ocean, such as the infrastructure construction and related industrial responsibility. 58 Kerguelen's location in the sub-Antarctic may deepen such considerations.…”
Section: Uncertainties About Publicmentioning
confidence: 99%
“…Ultimately, conversations across publics need to remain open and heterogenous, not polarized, to enable consideration of options. In addition, those who do attend to and/or recognize a broad set of perceived benefits for some ocean CDR options appear to hold that position and remain more steadfast as concerns acceptability in general and (largely) independent of political position (Satterfield et al, 2023).…”
Section: Political Worldviewsmentioning
confidence: 99%